GAMBARAN PERILAKU CARING PERAWAT PADA PASIEN DI RUANG RAWAT INAP INTERNIST RUMAH SAKIT SANTA ELISABETH MEDAN - Yosi Lorenza; Mardiati Barus; Maria Pujiastuti (STIKes Santa Elisabeth Medan, 2018)
The caring behavior of the nurse is the act of the nurse by showing compassion for the patient. Nurses who have caring for patients will establish interpersonal relationships so that patients feel comfortable, safe, and can improve their health.Goal: The purpose of this study is to find out how the description of caring behavior of nurses in patients in internal wards of Santa Elisabeth Hospital Medan.Method: Design of this study is descriptif. Population of the study is all inpatients in internis wards of Santa Elisabeth Hospital Medan. Sample is determined based on Slovin formula and obtained as much as 86 respondents.The sampling method used is probability sampling with random sampling type. Data collection techniques by distributing questionnaires directly to the respondents.Results: Results of this study is from 7 subscales obtained that the highest mean score is subscale assist in fulfillment of basic human need with score mean 3,45 and total mean score 3,17 in sufficient category.Conslution: Based on this study it can be concluded that the patient assessed the caring behavior of nurses in sufficient category of nursing care that has been given to the patient in the internal ward of Santa Elisabeth Hospital Medan.It is expected that the nurse will increase the caring and empathy in the patient.It is expected that nurses will increase caring and empathy to the patients by cultivating caring behavior through continuing education and practicing interpersonally.